Designer Exosomes for Targeted Delivery of a Novel Therapeutic Cargo to Enhance Sorafenib-Mediated Ferroptosis in Hepatocellular Carcinoma - Li, Xiaoju; Yu, Qianqian; Zhao, Runze; Guo, Xinyan; Liu, Chenlin; Zhang, Kuo; Zhang, Wangqian; Liu, Jinghan; Yu, Jinzheng; Wang, Shuning; Hao, Qiang; Li, Weina; et al. (Frontiers in Oncology, 2022)
Sorafenib is one of the few effective first-line drugs approved for the treatment of advanced hepatocellular carcinoma (HCC). However, the development of drug resistance is common among individuals with HCC. Recent evidence indicated that the anticancer activity of sorafenib mainly relies on the induction of ferroptosis. Furthermore, in our study, genes that suppress ferroptosis, especially GPX4 and DHODH, were enriched in sorafenib-resistant cells and primary tissues and were associated with poor prognosis of HCC patients who received sorafenib treatment. Therefore, a new ferroptosis inducer comprising a multiplex small interfering RNA (multi-siRNA) capable of simultaneously silencing GPX4 and DHODH was created. Then, exosomes with high multi-siRNA loading and HCC-specific targeting were established by fusing the SP94 peptide and the N-terminal RNA recognition motif (RRM) of U1-A with the exosomal membrane protein Lamp2b. The results from the in vitro and in vivo experiments indicate that this tumor-targeting nano-delivery system (ExoSP94-lamp2b-RRM-multi-siRNA) could enhance sorafenib-induced ferroptosis and overcome sorafenib resistance. Taken together, HCC-targeted exosomes (ExoSP94-Lamp2b-RRM) could specifically deliver multi-siRNA to HCC tissues, enhance sorafenib-induced ferroptosis by silencing GPX4 and DHODH expression and consequently increase HCC sensitivity to sorafenib, which opens a new avenue for clinically overcoming sorafenib resistance from the perspective of ferroptosis.